A Proposal of a Combined Convergence Regulatory Strategy Applied to Post-approval Changes by Latin American Countries, Reducing Workload and Allowing Continuous Improvement to Guarantee the Quality, Safety, and Efficacy of Medicines - Rodriguez, Heraclio; De Lucia, Maria Lucia (Frontiers in Medicine, 2021)
In recent years, post-approval changes (PACs) for medicinal products have increased faster than the national regulatory agencies can attend to without causing any negative impact. This study presents a proposal for regulatory management based on our analysis of the data available from the national regulatory agencies of Latin America on the total post-approval changes evaluated, and the time spent in the process. A retrospective search on the official websites of competent national regulatory authorities (NRAs) of 14 Latin American countries (México, Guatemala, Nicaragua, Honduras, El Salvador, Panamá, Costa Rica, Venezuela, Colombia, Ecuador, Peru, Argentina, Chile and Brazil) was conducted to collect data on post-approval changes in the last 4–6 years, up to January 2021. The NRAs considered were Brazil, México, Colombia, and Costa Rica. Our analysis was focused on the post-approval changes that required approval before implementation, those that were submitted, and those that were submitted and approved for small molecules, biologics, and biotechnological products. The results indicated differences in the regulatory processes and procedures applied by the different agencies. We also found that the implementation of the PACs was directly impacted by limited resources, which puts the medication supply for chronic treatments at risk resulting in serious consequences for patients. For local decision-making, Latin American NRAs should implement regulatory pathways already made by regulatory agencies included in the World Health Organization Listed Authorities on PAC approval to optimize their resources and to ensure the continuity of medicine supply for their patients.